Derajat Kesehatan Gigi dan Mulut Murid Sekolah Dasar di Kabupaten Bekasi, 1997/1998 - Yuyus Rusiawati; Magdarina Destri Agtini; F. Sintawati; Tommy M. Tommy (Faculty of Dentistry, Universitas Indonesia, 2015)
Oral dental epidemiological studies have shown the increasing of prevalence of dental caries and periodontal disease. This research was to find out base line data, among two groups of children from Urban and Rural of 20 elementary schools in sub district of Bekasi, West Java. Samples of 2205 children by the classes II, IV, V were observed 1065 in Urban and 1140 in Rural groups. The results show that prevalence of dental caries was 97,5%, DMF-T in Urban 2.225 and Rural 2.571 were significantly higher (p=0.0001) and those OHI-S in Urban 1.69^ were better than rural 2.059 (p=0.0000).